Effects of parameters of video head impulse testing on visually enhanced vestibulo-ocular reflex and vestibulo-ocular reflex suppression. Issue 8 (August 2020) - Soriano-Reixach, Maria Montserrat; Prieto-Matos, Carlos; Perez-Fernandez, Nicolas; Rey-Martinez, Jorge
Highlights: There is a quantifiable vestibulo-ocular reflex suppression (VORS) measured using video head impulse test devices. Visually enhanced vestibulo-ocular reflex and VORS test responses depend on head oscillation frequency. Participant concentration during VORS testing has significant effect VORS magnitude. Abstract: Objective: To investigate the main effects of some testing and analysis variables on clinically quantified visually enhanced vestibulo-ocular reflex (VVOR) and vestibulo-ocular reflex suppression (VORS) results using video head impulse test. Methods: This prospective observational clinical study included 19 healthy participants who underwent the VVOR and VORS tests. The effect of demographic variables, head oscillation frequency, rotation direction, visual acuity and analysis time window width and location of the recorded tests on the quantified results of both VVOR and VORS were evaluated. And specifically, for the VORS test the effect of cognitive reinforcement of the participant during testing was evaluated. Results: A statistically significant difference was observed among the VVOR, non-reinforced VORS, and reinforced VORS tests for mean gain values of 0.91 ± 0.09, 0.6 ± 0.15, and 0.57 ± 0.16, respectively ( p  < 0.001). The optimized linear mixed-effect model showed a significant influence of frequency on the gain values for the reinforced and non-reinforced VORS tests ( p  = 0.01 and p  = 0.004, respectively). Regarding the gain analysis method, statistically significant differences were found according to the short time interval sample location of the records for the initial location of the VVOR test ( p  < 0.006) and final location of the reinforced VORS test ( p  < 0.023). Conclusion: Significant differences were observed in the gain values according to VVOR and VORS testing. Head oscillation frequency is a significant factor that affects the gain values, especially in VORS testing. Moreover, in VORS testing, participant concentration has a significant effect on the test for obtaining suppression gain values. When a short time interval sample is considered for VVOR and VORS testing, intermediate time samples appear the most adequate for both tests. Significance: The quantified visually enhanced vestibulo-ocular reflex (VVOR) and vestibulo-ocular reflex suppression (VORS) tests have recently been added to the assortment of available clinical vestibular tests. However, despite the clinical validity of these quantified tests that appear to be of increasing clinical interest, the effects of most of the clinical testing methods and mathematical variables are not well defined. In this research we describe what are the main collecting and analysis variables that could influence to the VVOR and VORS tests. Specially for VORS test, participant concentration on test tasks will have positive effect on the measured vestibulo-ocular reflex (VOR) suppression.